Broadening of EM Energy-Absorption Frequency Band by Micrometer-to-Nanometer Grain Size Reduction in NiZn Ferrite - Fadzidah Mohd Idris; M. Hashim; I. Ismayadi; I. R. Idza; M. Manap; M. S. E. Shafie (IEEE, 2024)
Volume: 49 Issue: 11